اردو سیرت نگاری پر بیسویں صدی کے سیاسی اثرات : Interpretation of political influences on Seerah writing in 20th century - Hafiz Tasadduq Mahmood (AL-IDRAK JOURNAL, 2023)
If, on one hand, 20th century has turned out to be a symbol of advancements, then on the other hand it has also proved to be a birth place of a multitude of miseries and problems. In the 20th century, the rise in publishing of books led the knowledge and wisdom to the acme of excellence and brought the whole world in harmony. Europe, Africa, Asia and America seemed to walk a long way on the road to prosperity. When knowledge and wisdom became deeply rooted in the society then the progress of commerce and industry also became a constant factor. Although the life of prophet (PBUH) was deeply studied through the ages, but it was again the 20th century that shined brightly in this aspect too. Many Muslims and Non- Muslims scholars also penned down a lot of work on the Seerah of Muhammad (PBUH). As a result of, the refined form of Seerah writing appeared before the world. Seerah writing, like other branches of knowledge, came under the influence of modern age and witnessed many improvements. It was particularly influenced by the unique political environment of Indo-Pak subcontinent. These influences have been discussed in this article.